2018
DOI: 10.1002/smll.201703616
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effect of Structural Heterogeneity in Carbonized Electrospun Fibrous Mats for Flow Battery Electrodes by X‐Ray Tomography

Abstract: Electrospun custom made flow battery electrodes are imaged in 3D using X-ray computed tomography. A variety of computational methods and simulations are applied to the images to determine properties including the porosity, fiber size, and pore size distributions as well as the material permeability and flow distributions. The simulations are performed on materials before and after carbonization to determine the effect it has in the internal microstructure and material properties. It is found that the deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 53 publications
(73 reference statements)
3
42
0
Order By: Relevance
“…The electrospun materials were generated on a custom built electrospinner ,. The spin dope was pumped by a syringe pump through a connecting tube to a grounded needle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrospun materials were generated on a custom built electrospinner ,. The spin dope was pumped by a syringe pump through a connecting tube to a grounded needle.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the authors demonstrated the successful application of X‐ray micro‐CT to electrospun fibrous materials, producing virtual volumes of the mats for detailed computer modelling and assessment of the structural heterogeneity within the full thickness of the materials ,. The electrodes used in this study were composed of relatively large fiber sizes and displayed inhomogeneity through the thickness of the mat.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The pore network determines the morphology as a network of pores and throats where the pores act as reservoirs and the connecting throats define the transport pathways. Several groups have worked with pore network models in defining the transport through porous materials, in applications varying from fuel cell diffusion media,, PEM electrolyzers, redox flow battery electrodes, and rock structures . Banerjee et al .…”
Section: Introductionmentioning
confidence: 99%